The costs of networking in nonwork domains: a resource-based perspective. Issue 5 (17th June 2020) - Wolff, Hans-Georg; Kim, Sowon
Abstract : Purpose: While studies have established that networking is an investment in an individual's career that pays off, recent research has begun to examine the potential costs of networking. This study suggests that prior research is limited in scope, as it remains focused on the work domain. Drawing upon the work home resources model (Ten Brummelhuis and Bakker, 2012), the authors broaden this perspective and develop a framework of negative consequences in nonwork domains. The paper proposes that networking generates costs in nonwork domains, because it requires the investment of finite energy resources in the work domain, and people lack these resources in other domains. Design/methodology/approach: This study uses structural equation modeling of multisource data from N = 306 individuals and their partners to examine how networking affects two distinct nonwork outcomes: work–family conflict and work–life balance. Findings: Analyses support the general framework: networking is related to time- and strain-based work–family conflict, and work time mediates the relationship between networking and these forms of conflict. Moreover, networking exhibits an inverted U-shaped relationship with work–life balance, indicating that excessive networking as well as a lack of networking decrease work–life balance. Originality/value: This study adds to the emergent literature on the negative consequences of networking. The findings suggest that employees and organizations should adopt a broader and more balanced perspective on networking: one that takes the well-known benefits – but also potential costs in work and nonwork domains – into account.